PENGARUH PEMASARAN DIGITAL, INOVASI PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MI GACOAN OLEH MAHASISWA DI INDONESIA (STUDI PADA MAHASISWA YANG SUDAH PERNAH MAKAN MIE GACOAN) - Astuti, Ahkwila Yeni; Hardianto, Willy Tri; Agustim, Warter (Unitri Press, 2024)
The aim is to evaluate the influence of digital marketing, product innovation and brand image on purchasing decisions for Mie Gacoan in Indonesia, both partially and simultaneously. The method used is a quantitative descriptive approach. Sampling was carried out using the unknown population formula with a purposive sampling technique, with a focus on undergraduate students who had ever eaten gacoan noodles at any branch in Indonesia. The total sample was 100 respondents who filled out the questionnaire via Google Form. The data collected was analyzed descriptively using SPSS software. The results show that digital marketing, product innovation and brand image significantly contribute positively to purchasing decisions for Mie Gacoan in Indonesia.